(untitled) (Revue D’études Interculturelles De L’image, 2018)
Pim de la Parra (Paramaribo, 1940) is a seasoned and prolific Surinamese filmmaker with over 50 years of experience in independent feature filmmaking. His film career began in the Netherlands in the 1960s where De la Parra rapidly established himself as a charismatic pioneer of Dutch film. Together with his former school friend Wim Verstappen, he shook up the Dutch film industry by producing a profitable series of low-budget erotic feature films, of which Blue Movie (1971) still ranks in the top five of most successful Dutch theatrical films. This success enabled De la Parra to make two more expensive movies outside the Netherlands, one in his native Suriname. In the 1970s, the filmmaker produced Wan Pipel (1976), the first Surinamese feature film ever made; in 1980s, he made Odyssée d’Amour (1987), the first Dutch feature film set on the Dutch-Caribbean island of Bonaire. Both films flopped at the Dutch box office, which forced De la Parra to return to low-budget filmmaking. He became a master of what he calls the minimal movie and put out multiple films in only a few years’ time. In 1995, after successive disillusionments, De la Parra retired from the world of filmmaking and settled in Suriname. However, his passion for filmmaking remained strong and eventually led him to launch the Surinamese Film Academy in 2005. The Academy’s learning-by-doing program benefits from De la Parra’s extensive experiences in the field of low-budget filmmaking. In pursuit of his dream of a local film culture in Suriname and the rest of the Caribbean, the now 72-year-old filmmaker tirelessly passes on his pragmatic model ofminimal movie making to the next generation. This interview, which took place in two parts via Skype (January 18 and February 1, 2012), chronicles De la Parra’s long illustrious career spanning over five decades.